An Analysis of Lexical Relations in the Song ‘The Man Who Can’t Be Moved’ by The Script - Arta Jesika Rajagukguk; Bernieke Anggita Ristia Damanik (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the types of lexical relations found in the song “The Man Who Can’t Be Moved” by The Script and examines how these relations contribute to the song's overall meaning and emotional message. Employing a qualitative descriptive approach, data were collected through repeated listening to the song and systematic transcription of its lyrics. The analysis draws on the semantic theories of Yule (2010) and Lyons (1977) to identify and interpret three types of lexical relations: repetition, antonymy, and synonymy. The findings reveal that repetition is the most dominant lexical relation, appearing in more than 30 instances across eight distinct recurring phrases, functioning to reinforce the speaker's emotional persistence and unwavering devotion. Antonymy is found in ten contrasting pairs such as "broke" versus "broken-hearted" and "move on" versus "not moving" which highlight the emotional conflict at the heart of the song. Synonymy is identified in seven sets of near-synonymous words and phrases that create lexical variety while sustaining consistent meaning. These lexical relations collectively construct a rich semantic landscape that amplifies the song's themes of love, loyalty, and longing. The study concludes that lexical relations are powerful tools for meaning-making in song lyrics and that songs offer valuable material for semantic analysis in linguistics education.